UPAYA PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Alfian, Alfan (FIAT JUSTISIA, 2015)
Human trafficking is increasingly organized, the more troublesome the government to provide protection to the victim, because the crime became transnational, structured and systematic. From this incident it is important to be studied more deeply about the protection of victims of crime of trafficking in persons. The objective is to determine how the protection of victims of human trafficking crimes / human and determine the factors that constrain the government in protecting victims of human trafficking/ human. Legal protection against the crime of trafficking in persons in Indonesia is already regulated in such a way, but in terms of implementation of law enforcement, officials and government are still not seriously implies. Legal product that became a major locomotive and excellent law enforcement that the Criminal Code still not yet gives tendencies favor of the victim, because the product is still offering an abstract clause related casualties represented only by the state. Factors causing the difficulty of protection is not only on the government alone but the victims themselves who sometimes do omission because the first one is not able to react to deviations, the second, the victim or entity other controls may fear there will be a result of the more serious because of such conflict, the third, indifference has become a social climate that is caused by the absence of extensive reaction.Keywords: Crime, Legal Protection, Human TraffickingÂ